Effectiveness of Self-Regulation Fluid Program on Patients with Hemodialysis Self-Efficacy for Fluid Adherence in Al-Diwaniyah Teaching Hospital - Alaa Hamza Hermis; Rajaa Ibrahim Abed (Iraqi National Journal of Nursing Specialties, 2022)
Objectives: to evaluate patient knowledge with hemodialysis and to determine the effectiveness of Self-regulation Fluid Program on Patients with hemodialysis self-efficacy for fluid adherence in Al-Diwaniyah Teaching Hospital. Methodology: A quasi-experimental design (two group design: pre-test and post-test) was used. This study was conducted in Al-Diwaniya Teaching Hospital for the period from (15th of October 2018 to 20th of May 2019) on a non-probability (purposive) sample consisting of (60 patients) treatment in hemodialysis units. A questionnaire was built as a data collection tool and consisted of four parts: First part: Demographic characteristics of the patient that consisted of (7) items, second part: Clinical information of the patient that consisted of (8) items, third part: the self-efficacy scale of fluid control in hemodialysis patients that consisted of (22) items and fourth part: patients’ knowledge in two axis that consisted of (20) items. The validity of the questionnaire and the educational program were verified by presenting it to (18) experts. The sample has received a pre-test, educational program, and post-test. Descriptive and inferential statistics were used to analyze the results of the study using the Statistical Package of Social Sciences (SPSS) version 22 and Microsoft Excel (2010). Results: The study finding shows, that all the study sample responses at the pre-test were fair knowledge with a statistical mean of scores (1.35). Other than the post-test, shows (100%) of the study sample have high knowledge at the mean of scores (2.66). Also, the maturity of the patients in both groups (control and study) is female and age group (more than 48) years, most of them not read and write, the maturity of the sample of study marred, regarding to the monthly income is not sufficient and urban residency. The study also confirms that the effectiveness of an instructional program on patients with hemodialysis to enhance self-efficacy fluid control is positive. Conclusion: Program helps patients in increasing self-confidence, knowledge of Chronic Kidney Disease patient care including controlling fluid overload. Recommendations: The study recommended the necessity of activating the role of instructional program correctly in order to give about end stage renal disease, and conduct future research programs to improve the patient’s knowledge about end stage renal disease, fluid adherence and provide small booklist for caring.